Staphylococcus aureus Nasal Colonization in Preoperative Orthopaedic Outpatients - Price, Connie Savor (Springer-Verlag, 2008)
Nasal colonization with Staphylococcus aureus (SA) increases the risk of surgical site infection (SSI). We first (1) determined the prevalence of asymptomatic nasal colonization with SA, (2) assessed trends in methicillin resistance with time, (3) ascertained risk factors for nasal colonization; and (4) correlated SSI to nasal colonization status and procedure. We performed a cross-sectional analysis of SA nasal colonization among healthy preoperative orthopaedic outpatients between 2003–2005 who were within 2 weeks of surgery. Of 284 patients, 86 (30%) carried SA; of these, 81 (94%) were colonized with methicillin-sensitive and five (6%) with methicillin-resistant SA (MRSA). Total SA colonization increased from 25/78 (32%) in 2003 to 37/97 (38%) in 2005, and colonization with MRSA increased from 0/78 (0%) to four of 97 (4%), respectively. We found no associations between nasal carriage and demographics or procedures. Surgical site infection occurred in nine of 282 (3%), four of which were attributable to SA; these included 0/43 (0%) carriers who received decolonization with 2% mupirocin, two of 43 (4.7%) who declined decolonization, and two of 196 (1.0%) who were noncarriers. Nasal colonization with SA, including MRSA, among preoperative orthopaedic outpatients is increasing and their rates reflect community rates. Knowledge of colonization status may be important in decolonization, choosing perioperative or any subsequent empiric antibiotics.